2009
DOI: 10.4103/0970-9290.57359
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of endodontically treated teeth restored by different FRC posts: An in vitro study

Abstract: Significantly, cast posts and cores had a higher failure threshold including teeth fracture; whereas, fiber posts failure was due to core fracture, with or without fractures in coronal portion of posts. Difference in FRC posts did not provide any significant difference in the load failure and the mode of fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 24 publications
4
53
2
4
Order By: Relevance
“…18 Rigid metallic posts were responsible for stress concentration at the apical end and the coronal third of the canal wall, resulting in catastrophic vertical root fractures. 19 This finding is consistent with Kaur et al who demonstrated higher fracture with cast post compared to glass fibre post and composite core. 20 Our results confirm findings reported by Pasqualin et al 21 and Verrisimo et al 22 that the cast metal posts have a lower value of fracture resistance than fibre posts.…”
Section: Discussionsupporting
confidence: 90%
“…18 Rigid metallic posts were responsible for stress concentration at the apical end and the coronal third of the canal wall, resulting in catastrophic vertical root fractures. 19 This finding is consistent with Kaur et al who demonstrated higher fracture with cast post compared to glass fibre post and composite core. 20 Our results confirm findings reported by Pasqualin et al 21 and Verrisimo et al 22 that the cast metal posts have a lower value of fracture resistance than fibre posts.…”
Section: Discussionsupporting
confidence: 90%
“…Fiber posts have a low elastic modulus and are capable of dissipating stress, and can achieve strong bonding effects with the dentin through resin binder, forming a relatively homogeneous structure. Therefore, the fiber post is able to uniformly distribute the stress along the root, which will improve flexural capacity of the teeth and reduce the risk of root fracture [8,15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…(12) With the recent improvements in the dental materials, resin-based restorative materials with tooth-colored fiber post are of choice because of several advantages such as a suitable elastic modulus, esthetics, good bonding between post and cement, lower chair time, and minimal tissue removal. (13,14) The use of a fiber post with fractured teeth, as it interlocks the two fragments, minimizes the stress on the reattached tooth fragment. (13,14) Follow-up visits are critically important for all traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…(13,14) The use of a fiber post with fractured teeth, as it interlocks the two fragments, minimizes the stress on the reattached tooth fragment. (13,14) Follow-up visits are critically important for all traumatic injuries. The patient should be followed for 3, 6, 12 months and yearly for 5 years.…”
Section: Discussionmentioning
confidence: 99%